Interaksionisme Simbolik Aparatus Dan Pekerja Seks Di Bali - I Dewa Ayu S Joni; Ni Nyoman Dewi Pascarani; Tedi Erviantono (Universitas Islam Malang, 2019)
This article explores a form of symbolic interaction between the formal security apparatus of the State and sex workers in Bali. The study uses qualitative research methods with data collection methods for interviews and observations. Through this type of research traced the efforts of sex workers to communicate in order to negotiate their interests with the power represented by the local government security apparatus (apparatus). Sanders' (2001) and O'Neill's (2001) study shows sex workers are resistant to control. But in this capacity, sex workers have a communication style to negotiate activities with local state officials. Theory used symbolic interactionism from Blumer. In the field data obtained there are two types of meaning in symbolic interactions. Sex worker as a party spreading disease and violation of morality. Even this is used as building the meaning of the moral image of regional leaders. In this symbolic interaction meaning, sex workers with bureaucratic state apparatus are very dependent on social structures in society which depend on social status, involvement in sex trade organizations, and laws or policies related to the regulation of CSWs. Bali as a world tourism destination prioritizes the basic value of the development of cultural tourism and has never once declared it as sex tourism. It's just ironic that Bali is often used as a transit point for the existence of the trafficking industry before they depart overseas. Bali is used as the main transit of commercial sex workers in the women's trafficking network. Although in the interactionism the symbolic meaning of the repression of the state apparatus is still considered to manifest a patriarchal value system that provides more legal sanctions to service providers in this case sex workers, especially women, than their users, namely men.